Al6061합금의 PEO 피막 형성에 미치는 AC 전류밀도의 영향 - 박철기(Cheolgi Park); 문성모(Sungmo Moon); 정인모(Inmo Cheong); 윤대수(Daesoo Yun) (Biuletyn Uniejowski, 2019)
In this work, PEO (Plasma Electrolytic Oxidation) film formation behavior of Al6061 alloy was investigated as a function of applied current density of AC at 310 Hz in the range from $120mA/cm^2$ to $300mA/cm^2$ in 0.5 M $Na_2SiO_3$ solution. When applied current density is lower than a critical voltage of about $132mA/cm^2$, voltage reaches a steady-state values less than 120 V without generation of arcs and metallic color of the alloy surface remains. On the other hand, when applied current density exceeds about $132mA/cm^2$, voltage increases continuously with time and arcs are generated at more than 175 V, resulting in the formation of PEO films with grey colors. Two different types of arcs, large size and small number of arcs with orange color, and small size and large number of arcs with white color, were generated at the same time when the PEO film thickness exceeds about $50μm$, irrespective of applied current density. Formation efficiency of the PEO films was found to increase with increasing applied current density and the growth rate was obtained to be about $5μm/min$ at $300mA/cm^2$. It was also found that surface roughness of the PEO films with $70μm$ thickness is not dependent on the applied current density.